Cell-type-resolved transcriptomic landscape of human focal cortical dysplasia - Chuantao Fang; Yi Liu; Xiaodan Zhang; Ziwu Wang; Rongliang Guo; Jingjing Guo; Xianming Liu; Yanfeng Tan; Hao-jie Lu; Rui Zhao; Guilin Meng; Dashi Qi (Proceedings of the National Academy of Sciences, 2026)
Focal cortical dysplasia (FCD) is a major cause of drug-resistant epilepsy and displays substantial clinical and histopathological heterogeneity, yet the cellular and molecular bases underlying this diversity remain poorly defined. Here, we performed single-nucleus RNA sequencing of 487,286 nuclei from 34 paired lesional cores and perilesional cortices across FCD I-III, generating a cell-type-resolved transcriptomic atlas of human FCD. Comparative analyses identified both shared and subtype-specific transcriptional alterations across neuronal, glial, and vascular compartments. Inhibitory interneurons and deep-layer projection neurons exhibited prominent dysregulation, whereas astrocytes and vascular cells showed coordinated activation of inflammatory, metabolic, and hypoxia-responsive pathways. Several genes displayed consistent subtype-associated expression patterns, including ZNF254 , DRG1 , and ABHD17A in astrocytes, and ATF4 in endothelial cells. These results link cell-type-specific transcriptional programs to histopathological heterogeneity across FCD subtypes, identify candidate tissue-detectable markers, and provide insight into nonneuronal contributions to epileptogenic cortical malformations.